Netherton Syndrome Perspectives - Ellis Hon, Kam Lun; Cheung, Yuet Ching; Chan, Zoe Mireille; Law, Yan Tung; Lam, Hei Tung; Chu, Ashleigh; Leung, Alexander K.C.; Chandran, Nisha Suyien; Leong, Kin Fon (Current Pediatric Reviews, 2025)
Netherton syndrome (NS), also known as Comèl-Netherton syndrome, is a rare disorder of cornification resulting from pathogenic variants in the Kazal type 5 (<span class=
Keywords: congenital ichthyosiform erythroderma